Using the Interval Number TOPSIS Method to Assess the Risk of Water and Mud Inrush from Weathered Trough in Subsea Tunnels - Binghua Zhou; Yuxiao Huang; Shuai Wang; Chaojie Gu; Jisheng Cui; Baokai Yang; Zhongsheng Wang; Changsheng Du (Journal of Marine Science and Engineering, 2025)
Subsea tunnels cross complex geological structures, such as weathered troughs with fractured rock masses and high permeability, and are prone to water and mud inrush. To minimize the risk of subsea tunnelling, a novel method consisting of a multi-index evaluation system and a computational model using the interval number TOPSIS method was established. The multi-index evaluation system was formed by eight evaluation indices that can potentially affect water and mud inrush: sea depth, subsea tunnel burial depth, scale of weathering trough, interface angle, strength of surrounding rock, permeability of weathering trough, cyclical footage, and grouting reinforced region. The risk levels of water and mud inrush were divided into four grades. Considering the uncertainty of the evaluation indices, an evaluation vector of interval numbers was adopted. The triangular fuzzy number membership function was used to determine the membership degree, and the 1–9 scales method was used to construct the judgment matrices, which can obtain the weight of evaluation indices. Furthermore, the weight values of the evaluation indices combined with the membership degree were used to obtain the result vector, which can be analyzed using the interval number TOPSIS method. This novel assessment method was applied to the FWK15+350 of the Haicang tunnel successfully. The risk level fell into IV, which represents a high-risk section. The results showed a high degree of congruence with the prevailing circumstances, thereby validating the credibility of the proposed methodology.